Real-time broadband proton-homodecoupled CLIP/CLAP-HSQC for automated measurement of heteronuclear one-bond coupling constants. Issue 91 (14th September 2016) - Timári, István; Kaltschnee, Lukas; Raics, Mária H.; Roth, Felix; Bell, Nicholle G. A.; Adams, Ralph W.; Nilsson, Mathias; Uhrín, Dušan; Morris, Gareth A.; Thiele, Christina M.; Kövér, Katalin E.
Abstract : A new method is proposed that allows broadband homonuclear decoupled CLIP/CLAP-HSQC NMR spectra to be acquired at virtually no extra cost in measurement time. Abstract : A new method is proposed that allows broadband homonuclear decoupled CLIP/CLAP-HSQC NMR spectra to be acquired at virtually no extra cost in measurement time. The real-time (windowed) acquisition protocol applied follows a scheme recently devised for recording pure shift (broadband homonuclear decoupled) heteronuclear single quantum correlation (HSQC) spectra. To minimize systematic errors in the apparent coupling constants obtained using real-time homonuclear decoupling, we extended the acquisition scheme to include cycling of radiofrequency pulse phases both from chunk to chunk during windowed acquisition, and from scan to scan during time averaging, allowing robust coupling constant measurement. The new real-time pure shift CLIP/CLAP-HSQC experiments are designed to speed up coupling constant determination, to increase the sensitivity of measurement in favorable cases, and to simplify the extraction of accurate one-bond heteronuclear couplings from pure in- or anti-phase doublets using automatic peak picking. The scope and limitations of the method are discussed, and a variety of experimental tests are reported.